Electrospinning of polyacrylonitrile nanofibres with additives : study of orientation and crystallinity - Greyling, Corinne Jean (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2010.